2017
DOI: 10.1159/000485619
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Hypothyroidism Impact on the Characteristics of Patients with Polycystic Ovary Syndrome. A Meta-Analysis of Observational Studies

Abstract: Background/Aims: Definitive polycystic ovary syndrome (PCOS) diagnosis should exclude thyroid dysfunctions. The purpose of the study is to examine the impact of subclinical hypothyroidism on the characteristics of PCOS patients. Methods: A meta-analysis of the published observational studies was conducted. Medline, Scopus, and Cochrane database search was performed to identify the studies that compared euthyroid PCOS and subclinical hypothyroidism (SCH)-PCOS patients. A total of 9 studies were selected, totali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 45 publications
4
22
1
1
Order By: Relevance
“…We found no correlation of TSH with FBS as in contrast to the Bedaiwy et al study which showed an association between TSH and FBS [9]. De Medeiros et al showed normal FBS levels in the SCH group [22].…”
Section: Figure 1: Correlation Of Homa-ir With Tshcontrasting
confidence: 96%
“…We found no correlation of TSH with FBS as in contrast to the Bedaiwy et al study which showed an association between TSH and FBS [9]. De Medeiros et al showed normal FBS levels in the SCH group [22].…”
Section: Figure 1: Correlation Of Homa-ir With Tshcontrasting
confidence: 96%
“…Benetti-Pinto et al, and a meta-analysis also had similar observations. 13,14,16 Free testosterone was higher in euthyroid subjects with PCOS compared with SCH-PCOS in the study by Enzeveai et al 28 Both is assumed that presence of SCH in PCOS may be associated with higher metabolic risks. 1,5,10 In this study, we found that the euthyroid PCOS and SCH-PCOS groups had similar frequencies of acanthosis nigricans.…”
Section: Methodsmentioning
confidence: 93%
“…Previous studies have provided inconclusive results as to whether the presence of SCH in patients with PCOS has a higher CV risk than in patients with PCOS without SCH. [13][14][15][16] Data regarding the effect of SCH on clinical, hormonal and metabolic parameters in PCOS are insufficient, particularly within the context of Bangladesh. This study was conducted to explore whether the presence of SCH imparts higher reproductive and metabolic derangements in women with PCOS.…”
Section: Many Of These Reproductive Manifestations Of Pcosmentioning
confidence: 99%
“…In the long term, PCOS women with SCH might have increased risk of developing a variety of diseases. Total cholesterol (TC), triglyceride (TG) and fasting glucose were higher in PCOS with SCH ( 35 , 36 ), thus they are more likely to exhibit hyperlipidemia, impaired glucose metabolism, and cardiovascular diseases ( 24 , 37 ). SCH may also contribute to the psychological co-morbidities in women with PCOS, such as anxiety and depression, since the strong association between SCH, PCOS and depressive symptoms has been reported, respectively ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%